Alternative Seafood Networks During COVID-19: Implications for Resilience and Sustainability - Stoll, Joshua S.; Harrison, Hannah L.; De Sousa, Emily; Callaway, Debra; Collier, Melissa; Harrell, Kelly; Jones, Buck; Kastlunger, Jordyn; Kramer, Emma; Kurian, Steve; Lovewell, M. Alan; Strobel, Sonia; et al. (Frontiers in Sustainable Food Systems, 2021)
Export-oriented seafood trade faltered during the early months of the COVID-19 pandemic. In contrast, alternative seafood networks (ASNs) that distribute seafood through local and direct marketing channels were identified as a “bright spot”. In this paper, we draw on multiple lines of quantitative and qualitative evidence to show that ASNs experienced a temporary pandemic “bump” in both the United States and Canada in the wake of supply chain disruptions and government mandated social protections. We use a systemic resilience framework to analyze the factors that enabled ASNs to be resilient during the pandemic as well as challenges. The contrast between ASNs and the broader seafood system during COVID-19 raises important questions about the role that local and regional food systems may play during crises and highlights the need for functional diversity in supply chains.